Система впливів в публічному управлінні: теоретикометодологічний аспект - Матвєєнко Ірина Володимирівна (My University, 2024)
Дисертація є завершеною науково-дослідною роботою, в якій вирішена актуальна наукова проблема стосовно наукового обґрунтування теоретикометодологічних аспектів системи впливів в публічному управлінні та виробленні на цій основі практичних пропозицій щодо їх запровадження. Актуальність дослідження зумовлюється необхідністю перегляду теорії та методології впливів в публічному управлінні, формуванням нових теоретикометодологічних підходів до розуміння системи впливів в публічному управлінні, яка закладає концептуальне підґрунтя зміни поглядів на мету і способи існуючих в суспільних відносинах впливів. Сучасні перетворення в сфері державного управління та трансформаційні зміни, що пов’язані із запровадження правового режиму воєнного стану, обумовлюють зростання ролі та значення суспільства, в частині посилення його впливової функції при протистоянні військовій агресії та в процесах повоєнного відновлення України. В сучасних умовах державноуправлінський простір потребує нового методологічного наповнення щодо вироблення принципово новітнього підходу побудови взаємовідносин з суспільством. Акцентовано увагу на врахуванні досвіду країн, які зазнали війни та виробили ефективний підхід до цілісного відновлення соціальних та управлінських систем, на основі успішних стратегій впливу, з ефективними способами державного та громадського контролю за деструктивними та негативними впливами на суспільство і державу. За такої ситуації виокремлюється новий аспект та напрями дослідження щодо необхідності теоретико-методологічного обґрунтування концептуальних засад системи впливів в публічному управлінні. Dissertation for the degree of Doctor of Science in Public Administration, speciality 25.00.01 «Theory and History of Public Administration». - Dnipro University of Technology, Ministry of Education and Science of Ukraine, Dnipro, 2024. The dissertation is a completed research work that solves an urgent scientific problem regarding the scientific substantiation of theoretical and methodological aspects of the system of influences in public administration and the development of practical proposals for their implementation on this basis. The relevance of the study is determined by the need to revise the theory and methodology of influences in public administration, to form new theoretical and methodological approaches to understanding the system of influences in public administration, which lays the conceptual basis for changing views on the purpose and methods of influences existing in public relations. Contemporary transformations in public administration and transformational changes associated with the introduction of the legal regime of martial law are leading to an increase in the role and importance of society in terms of strengthening its influential function in countering military aggression and in the processes of post-war reconstruction of Ukraine. In contemporary conditions, the public administration space requires new methodological content to develop a fundamentally new approach to building relations with society. The author focuses on the experience of countries that have been affected by war and have developed an effective approach to the holistic restoration of social and governance systems, based on successful strategies of influence, with effective ways of state and public control over destructive and negative impacts on society and the state. In such a context, a new aspect and research areas are highlighted regarding the need for theoretical and methodological substantiation of the conceptual foundations of the system of influence in public administration.Матвєєнко І. В. Система впливів в публічному управлінні: теоретикометодологічний аспект : дис. … д-ра наук з держ. упр. : спец. 25.00.01 / Матвєєнко Ірина Володимирівна ; М-во освіти і науки України, НТУ «Дніпровська політехніка», Нац. Ун-т «Одеська політехніка». – Одеса , 2024. – 489 с.
The system of influences in public administration: theoretical and methodological aspect
Keywords: державне управління; впливи; публічне управління та адміністрування; система впливів; моделі впливів; типологія впливів; колективний вплив; колективний суб’єкт впливів; теоретична модель системи впливів; прикладна модель системи впливів; доктрина впливів; методика аналізу впливів; public administration; influences; public management and administration; system of influences; models of influences; typology of influences; collective influence; collective subject of influences; theoretical model for the system of influences; applied model for the system of influences; doctrine of influences; influence analysis methodology